2019
DOI: 10.1038/s41551-019-0484-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses to a photovoltaic subretinal prosthesis implanted in non-human primates

Abstract: Retinal dystrophies and age-related macular degeneration related to photoreceptor degeneration can cause blindness. In blind patients, although the electrical activation of the residual retinal circuit can provide useful artificial visual perception, the resolutions of current retinal prostheses have been limited either by large electrodes or small numbers of pixels. Here, we report the evaluation, in three awake non-human primates, of a previously reported near-infrared-light-sensitive photovoltaic subretinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 22 publications
5
51
0
3
Order By: Relevance
“…Early research has shown that photodiodes reliant solely on ambient light can induce neurotrophic effects, but are insufficient for phosphene generation (Chow et al, 2004;Palanker et al, 2005). By incorporating circuitry for signal amplification, significant responses were seen in animal models (Lorach et al, 2015;Prévot et al, 2019) and patients can perceive distinct phosphenes (Zrenner et al, 2010;Lorach et al, 2015). Since the image is based on incident light entering the eye instead of an externally located camera for MPDAs with electronic amplification, patients can utilize natural eye movements.…”
Section: Subretinalmentioning
confidence: 99%
“…Early research has shown that photodiodes reliant solely on ambient light can induce neurotrophic effects, but are insufficient for phosphene generation (Chow et al, 2004;Palanker et al, 2005). By incorporating circuitry for signal amplification, significant responses were seen in animal models (Lorach et al, 2015;Prévot et al, 2019) and patients can perceive distinct phosphenes (Zrenner et al, 2010;Lorach et al, 2015). Since the image is based on incident light entering the eye instead of an externally located camera for MPDAs with electronic amplification, patients can utilize natural eye movements.…”
Section: Subretinalmentioning
confidence: 99%
“…Most cutting-edge therapies today are directed toward late-stage rod-cone dystrophy and atrophic or wet AMD, where loss of photoreceptors has already occurred. For this, the lack of severe inherited models displaying outer retinal loss has been compensated by the generation of acute models via laser ablation (14-16), chemically induced photoreceptor ablation (16), or the separation of the outer retina in reaction to a subretinally implanted retinal prosthesis (17). Other promising vision restoration strategies such as optogenetics have been tested extensively in normal NHPs, including marmosets (18) and macaques (19,20).…”
Section: Uniqueness Of the Primate Model For Human Visionmentioning
confidence: 99%
“…These in vitro preparations allowed us to demonstrate functional expression of genes such as microbial opsins in cone photoreceptors (70) and retinal ganglion cells (73) in the development of optogenetic therapy for restoring vision. We also used ex vivo NHP retinal explants to assess the efficacy of the PRIMA photovoltaic retinal prosthesis (17). The recent development of retinal organoids from induced pluripotent stem cells (iPSCs) has extended the interest in in vitro studies by providing an unlimited source of human retinal cells, with the additional possibility of generating tissues from patients affected by specific gene mutations (72,(74)(75)(76)(77).…”
Section: Surrogate Models On the Development Pathmentioning
confidence: 99%
“…Engineered kidneys could potentially report on the level of metabolites within the blood and whether or not they can handle their excretion. Engineered retinas could allow restoration of vision and digitization of the recorded data for various purposes (Pré vot et al, 2019). For each of these engineered tissues or organs, the lifetime of the integrated electronics could also be controlled.…”
Section: Future Outlookmentioning
confidence: 99%